2018
DOI: 10.1111/odi.12868
|View full text |Cite
|
Sign up to set email alerts
|

Role of lactoferrin and lactoferrin‐derived peptides in oral and maxillofacial diseases

Abstract: The oral cavity harbors different taxonomic groups, the evolutionary coexistence of which develops the oral ecosystem. These resident microorganisms can alter the balance between the physiologic and pathologic conditions that affect the host, both locally and systemically. This highly sophisticated nature of the oral cavity poses a significant therapeutic challenge. Numerous human and animal studies have been conducted to potentiate the efficacy and competence of current treatments of pathologic conditions as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 168 publications
1
2
0
Order By: Relevance
“…Considering that lactotransferrin is widely recognised as a cariesassociated protein, we extracted one of its functional sequences and utilised a combination of synthesis strategies [38], including sequence modifications, de novo design, and template-assisted mimesis to design and obtain our experimental LF-1 and LF-2 peptides. To the best of our knowledge, both LF-1 and LF-2 demonstrated the most potent antibacterial and antibiofilm activity against dental caries among lactotransferrin and its derived peptides [17,39,40], corroborating the feasibility of our strategy regarding the rational extraction and modification of a functional sequence from existing caries-associated proteins and peptides. Lactoferrampin was adopted as the model peptide because it not only possesses antibacterial activity, but also characteristic structural features for the design of novel AMPs [19].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Considering that lactotransferrin is widely recognised as a cariesassociated protein, we extracted one of its functional sequences and utilised a combination of synthesis strategies [38], including sequence modifications, de novo design, and template-assisted mimesis to design and obtain our experimental LF-1 and LF-2 peptides. To the best of our knowledge, both LF-1 and LF-2 demonstrated the most potent antibacterial and antibiofilm activity against dental caries among lactotransferrin and its derived peptides [17,39,40], corroborating the feasibility of our strategy regarding the rational extraction and modification of a functional sequence from existing caries-associated proteins and peptides. Lactoferrampin was adopted as the model peptide because it not only possesses antibacterial activity, but also characteristic structural features for the design of novel AMPs [19].…”
Section: Discussionsupporting
confidence: 65%
“…Proteomic analysis has demonstrated that the levels of lactotransferrin were dramatically elevated in the acquired pellicle of caries-susceptible subjects [ 16 ], revealing its important role as a caries-associated protein. Although lactotransferrin can exert bactericidal action against S. mutans and mediate bacterial agglutination, markedly high concentrations are required to effectively perform an anticaries function [ 17 ]. The successful identification of several antimicrobial functional domains at the N-terminus of lactotransferrin has inspired the development of synthetic AMPs with a certain degree of antibacterial properties [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…(23,26) Lactoferrin is an iron-binding protein that can disrupt the nutrient uptake of oral pathogens. (23,27,28) With a balanced ecosystem intra-orally, the risks of mucosal irritation and in ammation due to microbial infections will be decreased, thereby improving the patient's comfort. Based on this concept, salivary substitutes incorporating the LP3 enzyme system are introduced in their range of products.…”
mentioning
confidence: 99%